Genome-wide analyses of the NAC transcription factor gene family in Acer palmatum provide valuable insights into the natural process of leaf senescence - Meng,Xin; Feng,Chun; Chen,Zhu; Shah,Faheem Afzal; Zhao,Yue; Fei,Yuzhi; Zhao,Hongfei; Ren,Jie (PeerJ, 2025)
Acer palmatum is a deciduous shrub or small tree. It is a popular ornamental plant because of its beautiful leaves, which change colour in autumn. This study revealed 116 ApNAC genes within the genome of A. palmatum. These genes are unevenly distributed on the 13 chromosomes of A. palmatum. An analysis of the phylogenetic tree of Arabidopsis thaliana NAC family members revealed that ApNAC proteins could be divided into 16 subgroups. A comparison of ApNAC proteins with NAC genes from other species suggested their potential involvement in evolutionary processes. Studies suggest that tandem and segmental duplications may be key drivers of the expansion of the ApNAC gene family. Analysis of the transcriptomic data and qRT‒PCR results revealed significant upregulation of most ApNAC genes during autumn leaf senescence compared with their expression levels in summer leaves. Coexpression network analysis revealed that the expression profiles of 10 ApNAC genes were significantly correlated with those of 200 other genes, most of which are involved in plant senescence processes. In conclusion, this study contributes to elucidating the theoretical foundation of the ApNAC gene family and provides a valuable basis for future investigations into the role of NAC genes in regulating leaf senescence in woody ornamental plants.
Keywords: Acer palmatum; Leaf senescence; Expression profile; NAC gene family; Phylogenetic analysis